Thermal Comfort in Built Environment: Challenges and Research Trends (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
To achieve the objectives of low-carbon and sustainable buildings, human thermal comfort and its related technologies are gaining increasing attention in recent years. This reprint focuses on two key issues of human thermal comfort: (1) a comprehensive scientific understanding of the intricate interplay between indoor occupants and their thermal environments, and (2) the technological advancements stemming from novel scientific breakthroughs. Special attention is given to thermal comfort in special spaces, of diverse groups, and with advanced technologies.